Four-day pulse of sodium cromoglycate modulates pulmonary vessel wall remodeling during 21-day hypoxia in rats - Novotný, Tomáš; Uhlík, Jiří; Vajner, Luděk (Experimental lung research, 2018)
AIM OF THE STUDY: Remodeling of pulmonary resistance arteries in rats due to 4-day hypoxia could be successfully suppressed by sodium cromoglycate. In this study, we tested the difference in the suppression between two distinct time patterns of cromoglycate administration during 21-day hypoxia. In the experiment, we focused on some details in both smooth muscle cells and extracellular matrix of pulmonary arterial walls. METHODS: During 21-day hypoxia, rats were treated with sodium cromoglycate either in the first four days or in the last four days. The first four days were chosen to test efficiency of an initial pulse of cromoglycate to suppress pulmonary vascular remodeling. The last four-day administration tested possibility to block remodeling post hoc. RESULTS: Initial pulse reduced and modified remodeling in all levels of pulmonary arteries, which comprises neomuscularization of prealveolar arteries, asymmetrical hypertrophy of tunica media in muscular pulmonary arteries and hypertrophy of tunica media and tunica adventitia in large conduit arteries. Terminal pulse had only negligible effect. CONCLUSIONS: Only the initial cromoglycate therapy led to significant morphological suppression of remodeling. We therefore assume important role of initial remodeling influencing during long time hypoxia experiment.
Keywords: krysa rodu Rattus; remodelace cév; myocyty hladké svaloviny; hypoxie; Animals; Pulmonary Artery; Vascular Remodeling; kromoglykát dvojsodný; Rats; extracelulární matrix; Extracellular Matrix; Myocytes, Smooth Muscle; Hypoxia; zvířata; arteria pulmonalis; Cromolyn Sodium